Closing the Gap: Executives and Student Perceptions of Leadership Characteristics for Health Care Managers. Issue 4 (October 2017) - Walter, Marcea L.
Abstract : A study was recently conducted to determine the perceptions of undergraduate health care management students regarding leadership characteristics that health care managers should possess to be successful. The results were then compared with a study that was conducted in 2012 of chief executive officers regarding their perceptions of the same leadership characteristics. The comparison of the studies was used to determine if the perceptions of the students and chief executive officers were similar or if the subjects considered different characteristics more important than others.